Assessing the use of ChatGPT among agri-food researchers: A global perspective - Mohammad Sadegh Allahyari; Sinisa Berjan; Hamid El Bilali; Tarek Ben Hassen; Soroush Marzban (Journal of Agriculture and Food Research)
This study examines the adoption of ChatGPT among agri-food researchers and experts across 61 countries, applying the Theory of Planned Behavior (TPB) to evaluate the key determinants of this adoption. Based on a quantitative methodology, an online survey was distributed to assess respondents' attitudes, subjective norms, perceived behavioral control, and willingness to utilize ChatGPT in their research practices. The findings reveal a predominantly positive attitude towards ChatGPT, with many participants acknowledging its potential to enhance research productivity through editing, translation, and communication tasks. However, subjective norms were found to have a lower influence, suggesting limited external pressure from peers or institutions to integrate ChatGPT. Path analysis demonstrated significant direct and indirect effects of attitude, subjective norms, and perceived behavioral control on willingness to adopt ChatGPT, with a Goodness of Fit index of 0.748 supporting the model's robustness. The study emphasizes the need for heightened awareness and advocacy within academic communities, along with targeted training and support to enhance perceived behavioral control and address concerns about the accuracy and reliability of outputs generated through artificial intelligence (AI). These insights provide valuable contributions to understanding the factors shaping the adoption of AI tools in academic research, particularly within the agri-food sector. Future research should explore the evolving landscape of AI adoption, regional and disciplinary differences, and the ethical considerations surrounding AI technologies. Addressing these issues will enable researchers to better harness the transformative potential of tools like ChatGPT to advance their work in agri-food research.